The mind at work : valuing the intelligence of the American worker - Rose, Mike (New York, 2004)
"This groundbreaking study finds that the intelligence, integrated skills and achievements of blue collar and service workers have been consistently undermined and marginalized by cultural stereotyping. Rose (Possible Lives) finds conventional assessment of intelligence tied to social class: to IQ tests that measure formal schooling rather than capacity, and judgments that elevate "mind work" such as teaching or surgery over so-called "body work" represented by hair stylists or plumbers. Rose demonstrates, through research and personal exploration of a variety of workplaces, that cognitive ability, including perception, judgment, memory and knowledge, is employed daily in the work of laborers like welders, carpenters and drivers. He includes an extraordinarily moving biography of his mother, who used timing, concentration, strategic efficiency and a high degree of social skills in her work as a waitress. He profiles vocational teachers such as Jim Padilla, who motivates and guides his student electricians while passing on the concentration, problem-solving skills and persistence necessary to success. Rose also provides an excellent overview of the academic-vocational divide and argues that its effacement is necessary for a more democratic society. Well written and perceptive, but never dogmatic, Rose's book puts an important and generally poorly covered piece of the U.S.'s sociological puzzle in bold relief. "